2003
DOI: 10.1128/iai.71.6.3463-3472.2003
|View full text |Cite
|
Sign up to set email alerts
|

AttenuatedYersinia pseudotuberculosisCarrier Vaccine for Simultaneous Antigen-Specific CD4 and CD8 T-Cell Induction

Abstract: Yersinia pseudotuberculosis employs a type III secretion system for targeting of several virulence factors directly to the cytosol of eukaryotic cells. This protein translocation mechanism mediates the ability of Yersinia to resist phagocytosis and is required for sustained extracellular bacterial replication. In the present study, the Yersinia outer protein E (YopE) was used as a carrier molecule for type III-dependent secretion and translocation of listeriolysin O (LLO) from Listeria monocytogenes. In compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 62 publications
0
46
0
Order By: Relevance
“…The development of an immune response depends on the amount of Ag that is translocated into the cytosol of APCs and it has been shown that hypertranslocation of heterologous Ag by a Y. pseudotuberculosis yopK knockout mutant results in a superior immune response (61). To exclude the possibility that the CD8 T cell response induced by yopP-deficient mutants could be the result of compensatory hypertranslocation of YopE/LLO/M45, we demonstrated by Western blot analysis that the deletion of yopP does not influence the amount of YopE/LLO/M45 that is translocated into DCs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of an immune response depends on the amount of Ag that is translocated into the cytosol of APCs and it has been shown that hypertranslocation of heterologous Ag by a Y. pseudotuberculosis yopK knockout mutant results in a superior immune response (61). To exclude the possibility that the CD8 T cell response induced by yopP-deficient mutants could be the result of compensatory hypertranslocation of YopE/LLO/M45, we demonstrated by Western blot analysis that the deletion of yopP does not influence the amount of YopE/LLO/M45 that is translocated into DCs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of LLO 91-99 -specific CD8 T lymphocytes in mice immunized with the Y. enterocolitica mutants was determined by an IFN-␥-specific ELISPOT assay as previously described (61). Assays were performed with nitrocellulose-backed 96-well microtiter plates (Nunc) that were coated with rat anti-mouse IFN-␥ mAb (BioSource International).…”
Section: Elispot Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggest that Y. pseudotuberculosis is a promising candidate for an oral live carrier vaccine, capable of stimulating antigen specific CD8 ϩ T-cell responses (40,41). Additionally, delivery of heterologous antigens by the type III secretion system (T3SS) in Y. pseudotuberculosis and Salmonella stimulated antigen-specific cytotoxic T-cell responses, antigen-specific CD8 ϩ memory T cells, and protection against challenge with different pathogens (40,42,43).…”
mentioning
confidence: 99%
“…Additionally, delivery of heterologous antigens by the type III secretion system (T3SS) in Y. pseudotuberculosis and Salmonella stimulated antigen-specific cytotoxic T-cell responses, antigen-specific CD8 ϩ memory T cells, and protection against challenge with different pathogens (40,42,43). Studies have indicated that both humoral immunity and cellular immunity contribute to vaccine efficacy against plague (21,24,(44)(45)(46)(47).…”
mentioning
confidence: 99%